Dante all’insegna dell’Unità - de Rooy, Ronald (Incontri. Rivista europea di studi italiani, 2011)
Dante in the straightjacket of the italian State In this article Dante’s literary and cultural reception are interpreted as being also indicative of the strength of Italy’s sociopolitical unity. From the beginning of the eighteenth century Dante and his poem have been used and misused repeatedly by cultural, literary and political key figures in order to forge and reinforce a national Dante. During Risorgimento Dante soon became the symbol of Italy’s political, moral and linguistic unity but he was also used, more implicitly, as a powerful antidote to the country’s disunity. After a period of more liberal and creative rewritings, the fascist regime and its scholars came up with an extremely reductive political and moral image of the Commedia and its poet. After the end of the second World War this fascist Dante was banned from national conscience and replaced with a myriad of creative rewritings. Poets like Eugenio Montale and Mario Luzi rediscovered and exploited Dante’s forgotten potential for Italian culture and literature; the work of important directors like Federico Fellini and Pier Paolo Pasolini could not exist without Dante; the venerable Lectura Dantis tradition was revived on television by famous actors and ultimately modernised and lightened by Roberto Benigni whose television performances also revive Dante’s role as a national and unifying symbol.